Multiple roles for notch in Drosophila myogenesis. - Fuerstenberg, S.; Giniger, E. (Developmental Biology, 1998)
Notch plays a role in many cell fate decisions in the developing Drosophila embryo, often at successive stages during the formation of a single tissue. In the embryonic mesoderm, Notch is involved in the process by which muscle progenitors are selected from a field of equivalent myoblasts. We have investigated the roles of Notch in somatic myogenesis and show that Notch can affect at least two additional steps in muscle development. Subsequent to the initial specification of progenitors, myoblast identity remains sensitive to mesodermal Notch activity until the time of fusion. Additionally, Notch is capable of suppressing muscle development nonautonomously by regulating a signal that emanates from the ectoderm.